PENILAIAN JUMLAH PENGGUNAAN TRUK ANGKUTAN DI DUA PERUSAHAAN HUTAN DI SUMATERA BARAT - Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
A study on the productivity of logging trucks at two forest companies was done in 1984, and the result is reported in this article. Four logging trucks used by PT Ragusa and five by PT Pasar Besar were selected randomly to study transport time and load volumes through work time study. The purpose is to find out the optimum number of trucks suitable to transport logs from the forests to log ponds, processing places or other distribution point. The result shows that:Isuzu TWD 20 trucks were used to transport logs at the two forest companies.The average log volume per and trip transportation at PT Ragusa and PT Pasar Besar were 15.20 m3 and 12.84 m3, respectively.Average productivity at PT Ragusa and PT Pasar Besar were 45.6 m3/day and 25.68 m3/day, respectively.Logging truck productivities were possibly influenced by load volumes and transport distance.The number of logging trucks actually urged in hauling logs at PT Ragusa and PT Pasar Besar were 5 and 11 units, respectively. Procurement of new or reparation of idle logging trucks is strongly recommended.